STRATEGIES AND NEW MODELS FOR SOCIAL DEVELOPMENT - Pejkovski, Jovan (Ревија за социјална политика/Journal of Social Policy, 2015)
Strategic planning is the process of formulating and implementingstrategies with which the organizations and the institutions are adjustedand influenced on the changes in the environment.Understanding of the future and the need for strategicdetermination of the conditions and possibilities for its achievement iscrucial question of each society.Creating a strategy cannot be understood as a magic solution to theproblems because it is a way to deal with the problems and risks that willappear in a structured way. Creating strategy represents a new way ofthinking, and accordingly creates new skills to be able to carry out theprocess. But it also must be flexible and adapt to the characteristics andspecifications of each organization.With including of the key elements of the strategic planningprocess successful strategic prediction is achieved aimed at decisionmaking procedure related to the organization of the system and theenvironment in the future.The impacts of globalization but also many internationalorganizations and funds will imply the needs for the preparation ofstrategies that are derived from strategic planning. Organizations,institutions, whether public or private, should be developed in subjects that